Characteristics of Hypertension in Children at Dr. Hasan Sadikin General Hospital Bandung in January to December 2014 - Meilani Meilani; Nanan Sekarwana; Yuni Susanti Pratiwi (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: Hypertension is often found in children. It could cause serious complications and added risk of hypertension in adulthood. Hypertension in children is likely secondary type and some of them might be severe. The aim of this study was to determine the demographic and clinical characteristics of hypertension in children admitted to Dr. Hasan Sadikin General Hospital Bandung in January to December 2014.Methods: The study design used was a quantitative, descriptive cross-sectional study. Data were obtained from medical records retrospectively of inpatient children from the period January to December 2014. Data were collected from the period September to November 2015 based on age and gender as a demographic characteristics and stage of hypertension, etiology of hypertension, and emerge of hypertensioncomplication as a clinical characteristics.Results: Ninety(1.9%)children with hypertension were found from 4,681 of total inpatient children consisting of 58 males and 32 females with median of age 8 (0−13) years old.The main stage of hypertension was hypertension stage 2 with 55 cases and nephrotic syndrome as the most common causes with 43 cases. The complications were present in hypertension stage 2 with 3 cases and hypertensive crisis with 2 cases.Conclusions: Children with hypertension are most commonly males and median of age was 8 years old. Hypertension is characterized by hypertension stage 2 and nephrotic syndrome as the most common etiology. Complications of hypertension appear in severe hypertension.